2014
DOI: 10.1002/jbmr.2360
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Volumetric Bone Density, Geometry, and Strength in Relation to 25-Hydroxy Vitamin D in Older Men

Abstract: Low serum 25‐hydroxy vitamin D (25(OH)D) concentrations are associated with increased hip fracture risk and decreased femoral areal bone mineral density (BMD) among elderly men. Structural dimensions of the proximal femur and volumetric BMD in cortical and trabecular compartments are also associated with hip fracture risk. However, associations of volumetric BMD or structural dimensions with serum 25(OH)D concentrations among older men remain unclear. In a random sample of 1608 men aged ≥65 years from the Oste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 41 publications
(130 reference statements)
0
16
0
1
Order By: Relevance
“…A recent article showed how in older men, higher levels of endogenous 25(OH)D may increase wholebone strength by increasing femoral volumetric BMD and cortical volume [31]. It would be very interesting to assess effects of vitamin D supplementation and of antiosteoporotic therapy on cortical index rather than BMD over time.…”
Section: Discussionmentioning
confidence: 98%
“…A recent article showed how in older men, higher levels of endogenous 25(OH)D may increase wholebone strength by increasing femoral volumetric BMD and cortical volume [31]. It would be very interesting to assess effects of vitamin D supplementation and of antiosteoporotic therapy on cortical index rather than BMD over time.…”
Section: Discussionmentioning
confidence: 98%
“…Even in the general population without PHPT, there are limited data using newer imaging modalities (such as cQCT and TBS) on the effect of vitamin D deficiency and insufficiency on skeletal health. In a subset of the MrOS study, 25OHD level was positively associated with integral vBMD and cortical volume at the hip as measured with cQCT in elderly men [37]. Standard clinical thresholds for vitamin D deficiency and insufficiency, however, were not utilized in this study and the effect of 25OHD level was small.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few other studies have reported an association between serum 25(OH)D and BUA [32, 37], but a significant number of studies have investigated this association with BMD as the outcome [2, 36, 3845]. The reports on this association do not agree across studies.…”
Section: Discussionmentioning
confidence: 99%